PERANCANGAN UI/UX DESIGN PADA APLIKASI JASA FREELANCER BERBASIS ANDROID MENGGUNAKAN METODE USER CENTERED DESIGN - Syahril Rizal R I; Surya Adi Saputra (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
Abstract : The growth of the information technology sector in Indonesia is relatively fast and will continue to grow, this will affect the way a business entity fulfills human resource needs to complete a project being carried out. Freelancers or freelancers are one solution for project owners who want employees to meet their human resource needs. One of the important factors in determining the success of a project undertaken by a freelancer is recruiting the right people to work on the project, but there are problems with clients towards freelancers, namely communication, turnaround time, and the payment system. So the authors took the initiative to design UI/UX Design for freelancer service applications where the application design is intended to meet 3 aspects of the problem, communication, turnaround time, and payment systems. In addition, application design is built using the UCD (User Centered Design) system development model so that applications are designed according to the objectives and meet user needs.